2018
DOI: 10.18203/2320-1770.ijrcog20183795
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of insulin resistance among infertile women with polycystic ovarian syndrome

Abstract: Background: Insulin plays a key role in producing hyperandronism and suppression of insulin secretion in women with PCOS is associated with decreased cytochrome P450c17α. cytochrome P450c17α is a bifunctional enzyme present in ovary is a key enzyme for androgen synthesis. Various studies have been conducted regarding association of insulin resistance with PCOS in infertile patients but there is no study is available about this in our area. So we have designed this study to evaluate insulin resistance in infert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Regarding infertility data of the studied cases (60), the mean infertility duration was 2.95(±0.85 SD) years, with majority of cases 71.7% (43/60) suffered from primary infertility. In the study done by Smitha et al (14) infertility lasted an average of 2.3625 years, and in a study by Dhagat et al (15) discovered that 70% (70/100) of the cases analyzed were affected by primary infertility, these findings corroborated those of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding infertility data of the studied cases (60), the mean infertility duration was 2.95(±0.85 SD) years, with majority of cases 71.7% (43/60) suffered from primary infertility. In the study done by Smitha et al (14) infertility lasted an average of 2.3625 years, and in a study by Dhagat et al (15) discovered that 70% (70/100) of the cases analyzed were affected by primary infertility, these findings corroborated those of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…19 Smitha et al has reported that the mean DHEAS concentration was higher in PCOS group this finding support our study. 20…”
Section: Resultsmentioning
confidence: 99%